Ethnomathematics: Exploration of Mathematics and Cultural Values in the Performing Arts of the Sasak Tribe Perisean - Lalu Muhammad Fauzi; Nila Hayati; Muhammad Gazali; Asri Fauzi (Hipotenusa : Journal of Mathematical Society, 2022)
Perisean art developed since the 13th century according to existing history, which started with a ritual to ask for rain when there was a long dry season which resulted in a famine. Perisean art performances are currently used as mere agility art performances. Pepadu is a term for players or fighters. The show is led by three referees, one pekembar tengaq (middle referee) who is in charge of leading the fight and two pekembar sedi (side referee) who is in charge of determining each pepadu. Perisean art is not only studied in the form of art but can also be studied as a form of contextual learning in mathematics. Thus, this study aims to explore the forms of mathematics and cultural values contained in the performing arts of perisean which can later be used as a source of contextual mathematics learning. This research is a qualitative research using ethnographic method. The informants used are traditional figures, pepadu, and cultural experts who understand the art of perisean , documentation and field notes. The findings show that in the performing arts of perisean in the tradition of the Sasak people there are mathematical ideas, namely geometric shapes found in perisean art instruments and musical instruments. which has the potential as a starting point in contextual mathematics learning.